If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y(2y + -9) + (2y + -9) = 0 Reorder the terms: 2y(-9 + 2y) + (2y + -9) = 0 (-9 * 2y + 2y * 2y) + (2y + -9) = 0 (-18y + 4y2) + (2y + -9) = 0 Reorder the terms: -18y + 4y2 + (-9 + 2y) = 0 Remove parenthesis around (-9 + 2y) -18y + 4y2 + -9 + 2y = 0 Reorder the terms: -9 + -18y + 2y + 4y2 = 0 Combine like terms: -18y + 2y = -16y -9 + -16y + 4y2 = 0 Solving -9 + -16y + 4y2 = 0 Solving for variable 'y'. Factor a trinomial. (-1 + -2y)(9 + -2y) = 0Subproblem 1
Set the factor '(-1 + -2y)' equal to zero and attempt to solve: Simplifying -1 + -2y = 0 Solving -1 + -2y = 0 Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -2y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -2y = 0 + 1 -2y = 0 + 1 Combine like terms: 0 + 1 = 1 -2y = 1 Divide each side by '-2'. y = -0.5 Simplifying y = -0.5Subproblem 2
Set the factor '(9 + -2y)' equal to zero and attempt to solve: Simplifying 9 + -2y = 0 Solving 9 + -2y = 0 Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -2y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -2y = 0 + -9 -2y = 0 + -9 Combine like terms: 0 + -9 = -9 -2y = -9 Divide each side by '-2'. y = 4.5 Simplifying y = 4.5Solution
y = {-0.5, 4.5}
| 2x/5-5=4 | | 3b^2+6b+3= | | f+43=120 | | 6n+21=4n+1 | | e-35=27 | | 0.000054s= | | d+19=83 | | k^2-36= | | f+27=49 | | 26/100= | | 0.10(y-8)+0.18y=0.12y-0.03(40) | | 3x^2+5x+k= | | 5+d=71 | | I=(1535)(.045)(3) | | 0.50x+0.80(60)=0.25(116) | | -20-40=-21/4 | | -40x+5y=30 | | -40=-21/4(x-20) | | (x-3/2)^2 | | -40=-21/4(x-20 | | x/3+2x/9+4x/27+8x/81+1=x | | 5p+(-6)= | | -sin(6x)=0 | | 3n^3/n^3 | | (-2r)(8)+(25)= | | 4/2-4/5= | | 9=8m+9 | | -3(-4-6y)+7(-4+5)=-8 | | 4/21*(145-y) | | X+(-4)+6x=3x+(-1)+5 | | 5-(x+7)=5x-8 | | 3+(y+2)+2(y-3)=-15 |